The Impact of Maternal Experience and Type of Feeding on Neonatal Jaundice in Phototherapy Unit - Jabar, Hind Farhan; Musihb, Zeki Sabah (Kerbala Journal of Nursing and Health Sciences., 2025)
One of the most prevalent issues in infants has a major impact on the mortality and morbidity of neonates. Neonatal jaundice (NNJ). Objectives: This study aimed to assess the effectiveness of different feeding methods in preventing neonatal jaundice, and to investigate the relationships between mothers’ experiences with neonatal jaundice and their sociodemographic variables. Methods: There is a quantitative descriptive study (cross-sectional) conducted in Karbala Teaching Hospital for Children in Holy Karbala City in Iraq for the period of 28th December 2024 to 2th February 2025. Nonprobability (convenience) sample of 130 mothers of with neonatal jaundice. A pilot study is used to assess the questionnaire's reliability, and a panel of experts is used to determine the questionnaire's content validity consisted from (11) experts. Data were analyzed and interpreted through use application of Statistical Package for Social Sciences (SPSS), version 26.0. Results: Results: The total maternal age shows a significant positive relationship with experience (r=0.346, p=0.001). Similarly, a mother's level of education (r=0.397, p=0.001). Mothers' occupation (r=0.252, p=0.004). Mothers have moderate (46.9%) to good (49.2%) levels of previous experience. There is a significant difference in feeding methods for preventing neonatal jaundice: breastfed (73.17), bottle-fed (63.39), and mixed-fed (63.88) infants. Conclusion: The outcome of the current study shows significant relationships between mothers' experience and various sociodemographic variables. Mothers' previous experience regarding neonatal jaundice ranged from moderate to good. Recommendations: Educating mothers by implementing educational programs for mothers about neonatal jaundice. Promoting proper feeding practices, encouraging mothers to exclusively breastfeed.